Diplomasi Keamanan Indonesia Terhadap Rezim Internasional ICAO: Studi Kasus Kawasan Perbatasan Batam Periode 2022-2025 - Awlia, Manda Putri; Alfajri, Alfajri (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
The shift in international security issues toward non-traditional dimensions positions aviation security as a strategic sector within the global system. This study aims to analyze Indonesia’s security diplomacy through compliance with the ICAO regime in Batam during the 2022–2025 period and its implications for international legitimacy. The method used is qualitative, employing a literature review and textual analysis based on secondary data. The results show that the implementation of standards is carried out through strengthened surveillance, enhanced security, and inter-agency coordination. This compliance reflects indirect security diplomacy as well as a strategy for building credibility. This study concludes that sustained compliance is an important instrument in strengthening Indonesia’s position in the international system.